Universality in the electroproduction of vector mesons - Baltar, Vera Lucia Vieira; Dosch, Hans Günter; Ferreira, Erasmo (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2011)
We study universality in the data of the electroproduction of vector mesons, using as guideline the results of a unified nonperturbative approach which reproduces well the available experimental data. After the extraction of factors that are specific of each vector meson, we arrive at a reduced integrated elastic cross-section which is universal. Our analysis suggests a finite infrared behavior for the strong coupling constant.